2015
DOI: 10.1190/int-2014-0280.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maturation on multiscale (nanometer to millimeter) porosity in the Eagle Ford Shale

Abstract: Porosity and permeability are key variables that link the thermal-hydrologic, geomechanical, and geochemical behavior in rock systems and are thus important input parameters for transport models. Neutron scattering studies indicate that the scales of pore sizes in rocks extend over many orders of magnitude from nanometer-sized pores with huge amounts of total surface area to large open fracture systems (multiscale porosity). However, despite considerable efforts combining conventional petrophysics, neutron sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…X-ray diffraction (XRD) data showed that calcite was the dominant mineral (96.3 per cent), followed by quartz (3.7 per cent), which likely explains the low anisotropy in the velocities observed for these samples. Previous studies also reported that Eagle Ford shale has a calcite-rich formation (Anovitz et al 2015). The tensile strength and permeability were measured in the directions perpendicular to the sedimentary plane, including the fracture propagation direction addressed in the present study (Section 3).…”
Section: Samplementioning
confidence: 93%
“…X-ray diffraction (XRD) data showed that calcite was the dominant mineral (96.3 per cent), followed by quartz (3.7 per cent), which likely explains the low anisotropy in the velocities observed for these samples. Previous studies also reported that Eagle Ford shale has a calcite-rich formation (Anovitz et al 2015). The tensile strength and permeability were measured in the directions perpendicular to the sedimentary plane, including the fracture propagation direction addressed in the present study (Section 3).…”
Section: Samplementioning
confidence: 93%
“…Details of the neutron small-angle scattering approaches have been reported elsewhere and are, therefore, summarized briefly. SANS and USANS were used to probe aggregate sizes from ∼100 Å to ∼15 μm.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…However, in the latter cases specialized masks, such as rectangular, slit (cf. NavarreSitchler et al 2013), or annular (Anovitz et al 2015b) shapes can be used. The images on the left shows a sample ground to 150 m, then fl oated off the glass slide (originally glued on using super glue) and attached to the Cd mask.…”
Section: Sample Preparationmentioning
confidence: 98%
“…Contrast matching experiments were used to demonstrate the presence of two phases, a zing-rich particle and a nanoporous carbon, the relative sizes of which were determined from the Q-dependence of the contrast curves. Such an approach (Anovitz et al 2015b) can also be used to analyze the pore surface mineralogy as a function of pore size, providing a link between porosity, overall mineralogy, and reactive mineralogy as a function of pore size and concentration. Figure 30.…”
Section: Contrast Matchingmentioning
confidence: 99%